Mathematical determination of electrical resistivity and Knight shift of liquid metals - K. N. Chhatkuli (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In the present work Harrison’s first principle technique, based on the concept of orthogonalised plane waves, has been successfully applied to compute various electronic and core interactions in order to obtain the Fourier transform of the crystal potential, termed as the form factor. The computed form factors have been consequently used to compute the physical properties through formulae developed by various authors in the past few decades.